2005
DOI: 10.1007/s00424-005-1489-0
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for AQP8 expression in the myoepithelium of rat submandibular and parotid glands

Abstract: Previously (Wellner et al., Pflugers Arch 441:49-56, 2000) we suggested that the localization of the aquaporins (AQPs) AQP5 and AQP8 in the apical and basolateral membranes of rat submandibular gland (SMG) acinar cells, respectively, provides for transcellular water flow during saliva formation. While the localization of AQP5 in this gland has been verified in several laboratories, there have been differing reports regarding AQP8 localization. Other investigators subsequently reported that AQP8 is not expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 9 publications
(17 reference statements)
1
18
0
Order By: Relevance
“…AQP4 is not detected, however, in immunofluorescence microscopy images of salivary gland cells (17). AQP8 is also a 28-kDa protein, and it is abundant in the testis (28), pancreas, and liver (19) and is expressed in the myoepithelial cells of rat submandibular and parotid glands (18). These findings indicate that AQP5 has a significant role in water secretion from serous acinar cells and interlobular duct cells of parotid and submandibular glands.…”
Section: Aquaporin Water Channel Proteins In Salivary Glandsmentioning
confidence: 85%
See 1 more Smart Citation
“…AQP4 is not detected, however, in immunofluorescence microscopy images of salivary gland cells (17). AQP8 is also a 28-kDa protein, and it is abundant in the testis (28), pancreas, and liver (19) and is expressed in the myoepithelial cells of rat submandibular and parotid glands (18). These findings indicate that AQP5 has a significant role in water secretion from serous acinar cells and interlobular duct cells of parotid and submandibular glands.…”
Section: Aquaporin Water Channel Proteins In Salivary Glandsmentioning
confidence: 85%
“…The AQP family consists of three subsets: aquaporins (AQP0, AQP1, AQP2, AQP4, AQP5, AQP6, and AQP8); aquaglyceroporins (AQP3, AQP7, AQP9, and AQP10); and superaquaporins (AQP11 and AQP12) (15,16). Among these members of the AQP family, AQP1, AQP3, AQP4, AQP5 (17), and AQP8 (18,19) are present in mammalian salivary glands. Hybridization studies indicate that AQP1, AQP3, and AQP5 mRNA are present at significant levels, but AQP4 is not detected (17).…”
Section: Aquaporin Water Channel Proteins In Salivary Glandsmentioning
confidence: 99%
“…However, studies in salivary glands, another exocrine glands that were very similar to LG anatomically and physiologically, showed that NKCC1 26,27 , CFTR 28 , and ClC2γ 22 play an important role in salivary secretion. Evans and colleagues 26 demonstrated that NKCC1 was localized to the basolateral membranes of acinar cells, but not duct cells, from parotid gland of wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, AQP1 is known to be localized in endothelial and myoepithelial cells (1,24) and AQP8 in myoepithelial cells (11,57), although their functions in the salivary gland are not fully understood. On the other hand, AQP5 is known to be localized at the apical membrane of secretory acinar cells of the submandibular, parotid, and sublingual glands (1,37) and is believed to be the molecule that plays a major role in the salivary secretion process (23,35,41,43).…”
mentioning
confidence: 99%